Study the Effect of Inhalation of Peppermint Oil on Depression and Anxiety in Patients with Myocardial Infarction who are Hospitalized in Intensive Care Units of Sirjan - AA Vaezi; S Parizi; AR Vahidi; H Tavangar (Journal of Medicinal Plants, 2017)
Background: A psychological reaction such as depression and anxiety is a complication of a heart attack. The aromatherapy is one of the processes in Complementary medicine to maintain mental health of diseases.